Resistance to populism. Issue 6 (18th August 2022) - Sato, Yuko; Arce, Moisés
ABSTRACT: Populist leaders mobilize supporters to accomplish the political transformations they seek to achieve. However, once they are in office, populist leaders also encounter mobilizations against them because of their exclusionary rhetoric as well as their attack on existing democratic norms. These populists' practices represent an erosion of (or threat to) political rights and move oppositional groups into struggle. Therefore, an increase in mobilizations under a populist leader can be seen as resistance to populism. Based on panel data analysis across 18 Latin American countries between 1990-2018, we find that populist rhetoric triggers a higher level of pro-democratic protests when it is combined with a populist leader's rejection of democratic norms. The findings are discussed in line with the political consequences of populism in contemporary Latin America.